THE PRACTICE REHEARSAL PAIR STRATEGY TOWARDS STUDENTS’ SPEAKING ABILITY AT THE TENTH GRADE STUDENTS OF SMA N 2 LUBUK ALUNG - Reza, Thenzia Februa; Hayati, Amal; Widyawati, Siska Okta (Jurnal Curricula, 2017)
The purpose of this research was to find the effect of the application of Practice Rehearsal Pairs strategy Towards Students’ Speaking Ability At The Tenth Grade Students of SMAN 2 Lubuk Alung. This research is an experimental research. The population was all students in class X SMAN 2 Lubuk Alung school year 2015/2016. The samples selected were X1class as the experimental class and X3 class as the control class. The research was conducted for 8 meetings. The research began by providing treatment to the experimental class by using Practice Rehearsal Pair strategy and control class by using conventional technique. At the end of the research, students were given a speaking test as an instrument to determine the result of the strategy used. The technique of analyzing data was the hypothesis t-test, which was used to test the difference in mean and standard deviation of the two samples. Based on the analysis of data obtained, tcalculate = 5.12 and ttable = 2.05. Because tcalculate (5.12) > ttable (2.05), then H0 was rejected and Hi was accepted, so it can be concluded that the application of Practice Rehearsal Pair strategy provides a significant effect towards students’ speaking ability at SMAN 2 Lubuk Alung.